Pseudopenilia bathyalis gen. n., sp. n. (Crustacea, Branchiopoda, Ctenopoda) — обитатель сероводородной зоны Черного моря - Сергеева, Н.Г. (Інститут зоології ім. І. І. Шмальгаузена НАН України, 2004)
Описан новый вид и новый род кладоцер отряда Ctenopoda, семейства Sididae. Этот представитель ветвистоусых, обнаруженный в анаэробной среде на предельных глубинах Черного моря (1900 и 2140 м), рассматривается как эндемик сероводородной зоны данного водоема. Он характеризуется наличием антеннул с пятью эстетасками, массивных плавательных антенн с базиподитом, имеющим ряд зубчатых выростов, и двучлениковых ветвей, вооруженных щетинками без сетул, 6 пар грудных конечностей относительно сходного строения и широкого постабдомена с крупными коническими коготка¬ми и постабдоминальными щетинками, также лишенными сетул. A new species and of a new cladocera genus of the order Ctenopoda (family Sididae) is described. It was found in the deep-sea anaerobic environment (1900 and 2140 m depths) and is considered to be an endemic of the hydrogen-sulphide zone of the Black Sea. The type material is deposited in the Department of Shelf Ecosystems of the Institute of Biology of the Southern Seas, NAS of Ukraine (Sevastopol). The new genus is characterized by short antennules with five aesthetascs, massive swimming antennae with basipodite having a number of protuberences and two-segmented branches with featherless setae, six pairs of thoracic limbs of more or less uniform structure, and wide postabdomen with large cone-shaped terminal claws and featherless postabdominal setae.